Caracterización de fincas hortícolas según el manejo de los cultivos, La Plata, Argentina - Stupino, Susana Andrea (2012)
The horticulture at La Plata horticultural belt, is driven by different management types that are named and classified with different criteria. One 2-type classification refers to farmers, farms or management types named conventional, and organic, based in the general, more distinctive features of management styles. Our preliminary general classification includes three management types. Moreover, the hypothesis is that farms, even though they may be classified into discrete types, integrate a management intensity gradient from conventional intensive (CI) to organic (ORG), with intermediate cases that may be described as low-input conventional (CBI).\nWe selected 33 farms with cultures at field, greenhouse or both. We made a poll to their farmers about number of years producing, cultivated area, species cultivated, management practices, and inputs (manures, synthetic fertilizers and pesticides, etc.); other open questions were related to the farmer perception, assumptions or knowledge about the reasons to do what he do. After a careful and comparative analysis of the chemicals, farming tools and equipment applied, most of the variables were expressed into ordinal scales. The ordinal classes indicate quantity and/or intensity of inputs, applications, tools, rotations and so on. A PCA analysis was performed to ordinate the data.